Metode Teknologi Fermentasi Pada Limbah Organik Makanan Sebagai Bahan Alternatif Tambahan Dalam Ransum Ayam Broiler - Putri Awaliya Dughita; Andri Haryono Awalokta Kusuma; Abdul Hakim; Bagus Andika Fitroh; Adib Norma Respati (Bulletin of Applied Animal Research, 2022)
his study aims to determine the effect of the method of fermentation technology on organic food waste as an additional alternative ingredient in broiler chicken dietary. The research was carried out in September 2018 at the physics and chemistry laboratory of the Universitas Islam Batik Surakarta. The research material uses restaurant food waste which is then fermented. The results of the proximate analysis of fermented food waste were BK 88.91%, Ash 8.94%, Protein 22.40%, Fat 5.96% and Crude Fiber 19.12%. Based on the results of proximate analysis, it shows that fermented food waste is included in protein source feed ingredients because it has a crude protein content of 20% or more, while restaurant waste fermentation has a crude protein content of 22.40%. The addition of 15% restaurant waste fermentation in broiler chicken rations can be done by adding other feed ingredients such as corn, soybean meal, fine bran, fish meal, palm oil, and premix. Keywords: food waste, broiler chicken dietary